(3ebOeI CHj GddjK aj GdUdGIs - (3GdSeQbfOj, CHh GddjK, EeGe GdgOi, fUQ Hf eMeO Hf CMeO Hf EHQGgje, (B373 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf bGd CHh GddjK GdSeQbfOj GYde Cf GdUdhI aQjVI bGFeI hTQjYI KGHJI YQaJ aQjVJgG HGdcJGH hGdSfI hELeGY GdCeIs
(3BNQgG (B:s
(3aXgQ GdaQb Hjf GdEjeGf hGdCYeGd HgPg GdCTjGA GdePchQjf (B( (3cPG (B) (3GdCYeGd GKfj YTQ UfaG efge ebje hefge eSGaQ hefge UMjM hefge eQjV Zfj habjQ MQ hYHOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8 / 27s
(3eYLe GdeDdajf (B4 / 24s
(3cTa GdXfhf (B2 / 1795s
(3gOjI GdYGQajf (B2 / 490s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs